2022
DOI: 10.3390/antib11030050
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Dependent Immunomodulation Induced by Antiviral Therapeutic Antibodies: New Perspectives for Eliciting Protective Immune Responses

Abstract: The multiple mechanisms of action of antiviral monoclonal antibodies (mAbs) have made these molecules a potential therapeutic alternative for treating severe viral infections. In addition to their direct effect on viral propagation, several studies have shown that mAbs are able to enhance the host’s adaptive immune response and generate long-lasting protective immunity. Such immunomodulatory effects occur in an Fc-dependent manner and rely on Fc-FcγR interactions. It is noteworthy that several FcγR-expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although NHPs are extremely useful to assess the protective effects of anti-HIV-1 mAbs [36,37], their use in the study of host immunity is limited by technical and cost considerations. In contrast, infection systems in mice offer many immunological tools and have allowed the dissection of several molecular and cellular mechanisms involved in the enhancement of host immune responses by antiviral mAbs (reviewed [16,17]). Using a mouse model of retroviral infection, Pelegrin and colleagues demonstrated that neutralizing antiviral mAbs act as immunomodulatory agents capable of stimulating protective immunity that persists long after the end of treatment (more than 1 year).…”
Section: Mechanisms Involved In the Enhancement Of Adaptive Immune Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although NHPs are extremely useful to assess the protective effects of anti-HIV-1 mAbs [36,37], their use in the study of host immunity is limited by technical and cost considerations. In contrast, infection systems in mice offer many immunological tools and have allowed the dissection of several molecular and cellular mechanisms involved in the enhancement of host immune responses by antiviral mAbs (reviewed [16,17]). Using a mouse model of retroviral infection, Pelegrin and colleagues demonstrated that neutralizing antiviral mAbs act as immunomodulatory agents capable of stimulating protective immunity that persists long after the end of treatment (more than 1 year).…”
Section: Mechanisms Involved In the Enhancement Of Adaptive Immune Re...mentioning
confidence: 99%
“…Fc-FcgR interactions can also directly affect viral propagation through other mechanisms, such as antibody-dependent cellular viral inhibition. In addition, upon opsonization of viral targets and formation of immune complexes (ICs), engagement of FcgRs by antiviral mAbs has been shown to have immunomodulatory effects leading to the induction of protective immunity ('vaccinal effect') (reviewed in [16,17]). These immunomodulatory effects have been reported in several preclinical models of viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mAbs can form immune complexes (ICs) via binding with different viral determinants (virions or infected cells) and the subsequent engagement of FcγRs by ICs has immunomodulatory effects leading to the induction of protective immunity. 4 We have previously identified different FcγR-expressing immune cells involved in the vaccinal response during mAb-based therapies (8,9). By using a mouse model of retroviral infection, we have shown a key role for ICs in enhancing antiviral immune responses by multiple innate immune cells such as dendritic cells (DC) (17,18), neutrophils (19,20), monocytes (20) and NK cells (21) in a FcγR-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified different FcγR-expressing immune cells involved in the vaccinal response during mAb-based therapies (8,9). By using a mouse model of retroviral infection, we have shown a key role for ICs in enhancing antiviral immune responses by multiple innate immune cells such as dendritic cells (DC) (17,18), neutrophils (19,20), monocytes (20) and NK cells (21) in a FcγR-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation